2021
DOI: 10.1002/star.202100190
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Traits and Physicochemical Properties of Starch of Different Grain Positions in Wheat Spike Under Nitrogen Treatment

Abstract: Nitrogen is an important factor that influences the yield and quality of wheat grain. However, little is known about its effect on the different positions of the grain in spikelets. Compared with the control group, nitrogen application increased the weight, starch content, and protein content of grains in each position considerably. In particular, the protein content in high grain positions of Yangmai 13 (YM 13) under nitrogen treatment are similar to those positions in Yannong 19 (YN 19) under normal levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…The lack of carbohydrate supply and the limitation of storage capacity resulted in differences in grain weight at different spikelet positions. In spikelets, the first and second welldeveloped grains are considered superior grains, while three or more maldeveloped grains are considered to be inferior grains (Wang et al 2021a). The superior grains flowered early and were located in the middle of the spikelet, while the inferior grains flowered later and were mainly located at the bottom and top of the spikelet.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of carbohydrate supply and the limitation of storage capacity resulted in differences in grain weight at different spikelet positions. In spikelets, the first and second welldeveloped grains are considered superior grains, while three or more maldeveloped grains are considered to be inferior grains (Wang et al 2021a). The superior grains flowered early and were located in the middle of the spikelet, while the inferior grains flowered later and were mainly located at the bottom and top of the spikelet.…”
Section: Discussionmentioning
confidence: 99%
“…The waxy maize starch pasting and thermal properties are affected by N fertilization and starch with large starch granule size (SGS) exhibit high trough (TV), final (FV), and setback (SB) viscosities and gelatinization temperatures [ 5 ]. Studies on wheat [ 6 , 7 ], common buckwheat [ 8 , 9 ], Tartary buckwheat [ 10 , 11 ], and rice [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ] have reported that starch pasting and thermal qualities of cereal grain are affected by N rates, split times, application stages, and the ratio of base fertilizer to topdressing application via changes in the grain composition contents and starch structures such as SGS, amylopectin chain-length (ACL), and relative crystallinity (RC).…”
Section: Introductionmentioning
confidence: 99%